“ENHANCING URBAN LANDSCAPES THROUGH TERRAIN AND NATURAL ELEMENTS: INTERNATIONAL AND LOCAL PRACTICES” - Eshmamatov Xushnudbek Obidjonovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines the application of terrain and natural elements in urban landscape design to improve ecological sustainability, aesthetic quality, and recreational opportunities. It analyzes how hills, slopes, valleys, and artificial elevations can define functional zones, guide pedestrian movement, and create visual focal points. Water features and vegetation are discussed for their role in supporting biodiversity, regulating microclimates, and enhancing public spaces. The study reviews international practices from Europe and North America alongside local implementations in Central Asia, highlighting strategies for integrating terrain and natural elements to develop sustainable, multifunctional, and visually engaging urban landscapes.